2012
DOI: 10.1007/s10072-012-1149-z
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose nicotine facilitates spatial memory in ApoE-knockout mice in the radial arm maze

Abstract: Here, we investigated the effects of nicotine on spatial memory in ApoE-knockout (ApoE-KO) and wild-type (WT) mice in a radial arm maze. Training occurred on three consecutive days and the test was performed on day 4, with one trial per day. Then on day 4, animals were administered nicotine (0.1, 0.25, 0.5, and 1.0 mg/kg) or the antagonist of nicotinic receptors (nAChRs) mecamylamine (MEC 2 mg/kg) alone or together with 0.1 mg/kg nicotine. The number of errors in the first eight choices was recorded. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Stimulation of the cholinergic system by nicotinic acetylcholine receptor (nAChR) agonists protects against glutamate-mediated neurotoxicity and leads to subsequent cognitive improvement in rodent models of neurodegenerative disorders [ 20 ]. A low dose of nicotine enhances cognitive performance by attenuating the impairment of cholinergic neurotransmission [ 21 , 22 ]. Experimental treatment of neurodegenerative disorders shows that nicotine mediates neuroprotection against NMDA-mediated excitotoxicity in the neurons by calcium-dependent mechanisms via neuronal α4β2- and α7-containing nAChRs [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of the cholinergic system by nicotinic acetylcholine receptor (nAChR) agonists protects against glutamate-mediated neurotoxicity and leads to subsequent cognitive improvement in rodent models of neurodegenerative disorders [ 20 ]. A low dose of nicotine enhances cognitive performance by attenuating the impairment of cholinergic neurotransmission [ 21 , 22 ]. Experimental treatment of neurodegenerative disorders shows that nicotine mediates neuroprotection against NMDA-mediated excitotoxicity in the neurons by calcium-dependent mechanisms via neuronal α4β2- and α7-containing nAChRs [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Spatial memory of the radial arm maze and Morris water maze can be improved in unimpaired animals by the administration of nicotine and this effect can be blocked by the administration of the nAChR antagonist mecamylamine [167][168][169], indicating that the performance enhancing effects of nicotine are nAChR dependent. Additionally, nicotine improves performance in several models of impaired spatial memory.…”
Section: Spatial Memorymentioning
confidence: 96%
“…Additionally, nicotine prevents the adverse effects of stress and Ab infusion on performance in the submerged radial arm maze [172,173]. In the Morris water maze, nicotine administration attenuates spatial learning deficits in lead-exposed animals [174], reverses AF64A-induced and sodium metavanadate-induced deficits in Morris water maze performance and improves Morris water maze performance in Apo-E knockout mice [169,175,176].…”
Section: Spatial Memorymentioning
confidence: 98%
“…Nicotine administration is known to improve a variety of cognitive functions (Rezvani and Levin 2001). In particular, the effect on WM has been reported in rodents (Rushforth et al 2011), pigeons (Kangas and Branch 2012), monkeys (Buccafusco et al 1999;Buccafusco and Terry 2004), and humans (Heishman et al 2010;Kangas and Branch 2012;Levin et al 1996;Spinelli et al 2006;Sultana et al 2013;Upright and Baxter 2021). Katner et al (2004) examined the effects of nicotine in monkeys trained on a variety of WM tasks and found that performance improved regardless of memory domain, with more difficult conditions showing a greater effect.…”
Section: Effects Of Nicotinic Achr Agonist and Antagonistmentioning
confidence: 99%